Curcumin Inhibits Transforming Growth Factor β Induced Differentiation of Mouse Lung Fibroblasts to Myofibroblasts - Liu, Daishun; Gong, Ling; Zhu, Honglan; Pu, Shenglan; Wu, Yang; Zhang, Wei; Huang, Guichuan (Frontiers in Pharmacology, 2016)
Transforming growth factor β (TGFβ) induced differentiation of lung fibroblasts to myofibroblasts is a key event in the pathogenesis of pulmonary fibrosis. This study aimed to evaluate the effect of curcumin on TGFβ induced differentiation of lung fibroblasts to myofibroblasts and explore the underlying mechanism. Mouse lung fibroblasts were cultured and treated with TGFβ2 and curcumin or rosiglitazone. Cell vitality was examined by MTT assay. The secretion of collagen-1 was assessed by ELISA. α smooth muscle actin (αSMA) was visualized by immunofluorescence technique. The expression of peroxisome proliferator activated receptor γ (PPARγ) and platelet derived growth factor R β (PDGFRβ) was detected by PCR and Western blot analysis. We found that curcumin and rosiglitazone inhibited the proliferation and TGFβ induced differentiation of mouse lung fibroblasts. In addition, curcumin and rosiglitazone inhibited collagen-1 secretion and αSMA expression in mouse lung fibroblasts. Furthermore, curcumin and rosiglitazone upregulated PPARγ and downregulated PDGFRβ expression in mouse lung fibroblasts. In conclusion, our study reveals novel mechanism by which curcumin inhibits TGFβ2 driven differentiation of lung fibroblasts to myofibroblasts. Curcumin could potentially be used for effective treatment of pulmonary fibrosis.